Effects of amphiphilic pluronic F127 on the performance of PS/SPEEK blend ultrafiltration membrane: Characterization and antifouling study. (August 2017) - Teli, Shivanand B.; Benamor, Abdelbaki; Nasser, Mustafa; Hawari, Alaa; Zaidi, Syed Javaid; Ba-abbad, Muneer; Mohammad, Abdul Wahab
Graphical abstract: Highlights: Synthesis of Sulfonated Poly(ether ether ketone) (SPEEK) from Poly(ether ether ketone) using H2 SO4 as sulfonation agent. Preparation of Polysulfone/SPEEK blend membrane with different proportions of Pluronic F-127 pore forming agent. Effect of SPEEK-Pluronic F-127 addition into the Polysulfone blend membrane. Permeability and anti-fouling properties of PSf/SPEEK-Pluronic F-127 blend membrane were found to be superior than those of pure PSf/SPEEK membrane. Abstract: The effect of amphiphilic Pluronic F127 additive on the ultrafiltration performance of polysulfone (PSf)/sulfonated poly (ether ether ketone) (SPEEK) blend flat sheet membranes was investigated in the present work. Fixed amount of SPEEK was used throughout the experiments to improve the PSf membrane surface performance and permeability properties. The addition of various proportions of Pluronic F127 was used to improve the hydrophilic characteristics of blend PSf/SPEEK membranes. It was found that membranes surface hydrophilicity, surface roughness, equilibrium water content and pores size increased with increasing Pluronic F127 concentration in the blend. The increase of Pluronic F127 additive in the blend changed the membrane morphology from finger-like to sponge-like structure. performance of the membranes were evaluated in terms of pure water, humic acid (HA) and bovine serum albumin (BSA) permeation fluxes which were found to increase with increased Pluronic F127 concentration. The BSA was used as a model foulant to investigate flux rejection and flux recovery ratio (FRR%). The PLU-5.5 membrane achieved the highest BSA rejection (97.55%) with FRR (78.18%) values.